Research Strategies and Media Relations in Public Relations Practices - Rachmat Kriyantono (KOMUNIKATIF : Jurnal Ilmiah Komunikasi, 2019)
This study aims to describe the strategies of private and government public relations practitioners in research and media relations. Some literature states that the practice of public relations begins and ends with research and media relations is crucial to the success of the practice of public relations. In this era of openness, the quality of research and media relations is increasingly demanding high attention. The researcher formulated the assumption that public and private PR have conducted research as the basis of their activities and media relations has been carried out on the principle of information disclosure. This study uses a qualitative method by conducting interviews with 32 public relations practitioners in East Java, and comes from universities, state-owned enterprises, and private companies. The results of this research are in the form of a proposition that practitioners have not given the focus of conducting research related to the quality of media relations, public relations universities have a tendency to make mass media as the main target while practitioners from private companies or state-owned enterprises tend to place leaders as the main public, and public relations practitioners tend to aim at reducing negative coverage as a media relations strategy rather than building long-term relationships. This research has contributed to the study of public relations in the Indonesian context related to the quality of research and media relations conducted by public relations practitioners.